Predicting seat transmissibility of seated human body on suspension seat exposed to vertical whole-body vibration - Adam, Siti Aisyah (2020)
Exposure to a whole-body vibration is an occupational risk factor, which leads to research interests in biodynamic responses of a human body. The knowledge of biodynamic responses of a seated human body on a suspension seat are limited as previous studies were merely focused on the rigid and conventional seats. The main objective of this thesis is to predict the seat transmissibility of a seated human body on the agriculture suspension seat. In addition, factors affecting the seat transmissibility and the apparent mass, such as postures and vibration magnitudes are also investigated. In the first experiment, the vertical seat transmissibility and the Seat Effective Amplitude Transmissibility (SEAT) values were measured. Eleven healthy male subjects aged between 21 to 35 years old, with a mean weight and height of 61.5 kg, and 1.68 m, respectively participated in the study. All the subjects were exposed to random vertical vibration in the range of 1 to 20 Hz, at three vibration magnitudes (0.5, 1.0 and 2.0 m/s2 r.m.s.) for 60 s. For each exposure, four postures were investigated (“relax”, “slouch”, “tense”, and “backrest”). The results showed that the primary resonance frequency of the seat transmissibility for every posture was pronounced between 1.7 and 2.5 Hz. The transmissibility at the resonance was the highest for the “backrest” condition. The results of SEAT values revealed that “slouch” posture showed the highest value (64.7%). In the second experiment, the apparent mass of a seated human body on a rigid and suspension seat were measured. Two sitting conditions were investigated – i) without the backrest and ii) with the vertical rigid backrest. The experimental measurement revealed a lower peak magnitude and resonance frequency of apparent mass without the backrest for a suspension seat (4.0 to 5.2 Hz), as compared to those measured with a rigid seat (4.5 to 5.4 Hz). For both seats, there was a reduction in the peak of apparent mass when in contact with a backrest. In both experiments, there was a reduction in the primary resonance frequency of the seat transmissibility and the apparent mass with an increase in the vibration magnitude, suggesting a non-linearity in the suspension seat-human system. Using the measured apparent mass of the seated human body on suspension seat, a two-degree-of-freedom lumped parameter model was developed. The model was able to fit the measured responses of the body in various sitting conditions (with and without the backrest). The modelling found that when a human body was in contact with the backrest, the mass decreased and the stiffness increased, resulting in an increase in the derived damped natural frequency. A combined three-degree-lumped-parameter of suspension seat-human body model was developed to predict the suspension seat transmissibility. The model was capable in predicting the seat transmissibility by minimizing the sum-of-least-squares error between the experimental measurements and the model prediction. It was found that the performance of the suspension seat did not depend on the suspension mechanism alone, but rather on the combination of the seated human body with the suspension seat. This research shows that the vibration transmission of a suspension seat can be predicted. Such predictions will assist the optimization of the suspension seat, and thus reduce the time needed to assess the suspension seat performance.